2022
DOI: 10.3389/fmed.2022.894541
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of visual acuity improvement after phacoemulsification cataract surgery

Abstract: PurposeThis study aimed to assess preoperative predictors of visual outcome after phacoemulsification cataract surgery in Jordan, a Middle Eastern country.MethodsThis was a retrospective longitudinal study of adult patients who underwent phacoemulsification cataract surgery from January 2019 to July 2021. For each patient, we included only the first operated eye. We obtained pre-operative ocular history, cataract surgery complication risk based on a predesigned score, visual acuity, best correction, and best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…This study found that all patients who underwent phacoemulsification showed a visual improvement one month after surgery. A study reported a visual improvement of 0.33 after surgery (95% CI: [0.31, 0.35]), with the predictor of ocular comorbidities such as diabetic retinopathy, glaucoma, and complication risk factors (i.e., high-risk surgery) (AlRyalat et al, 2022), age category (<40 years old), duration of operation (>60 minutes), or surgery without IOL (Sa'at et al, 2022). A study in Bali reported a visual acuity improvement with zero cases of blindness remaining.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that all patients who underwent phacoemulsification showed a visual improvement one month after surgery. A study reported a visual improvement of 0.33 after surgery (95% CI: [0.31, 0.35]), with the predictor of ocular comorbidities such as diabetic retinopathy, glaucoma, and complication risk factors (i.e., high-risk surgery) (AlRyalat et al, 2022), age category (<40 years old), duration of operation (>60 minutes), or surgery without IOL (Sa'at et al, 2022). A study in Bali reported a visual acuity improvement with zero cases of blindness remaining.…”
Section: Discussionmentioning
confidence: 99%
“…However, posterior capsular opacification and macular edema collectively constituted 20%, while optic atrophy, glaucoma (a set of disorders that damage the optic nerve of the eye, resulting in vision loss [ 21 ]), and retina hemorrhage each represented 10% of cases with poor vision. A previous study that assessed predictors of visual outcome after phacoemulsification cataract surgery reported that significant predictors that affect improvement in visual acuity included the presence of diabetic retinopathy, glaucoma, and high-risk surgical complications [ 29 ]. Furthermore, a study of the European Registry of Quality Outcomes for Cataract and Refractive Surgery found that ocular comorbidities such as macular degeneration, glaucoma, diabetic retinopathy, amblyopia, and others were the most important predictors of improvement in visual acuity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%